PENGAWASAN DINAS PERHUBUNGAN TERHADAP JURU PARKIR DI TEPI JALAN UMUM BERDASARKAN PERATURAN DAERAH KOTA DUMAI NOMOR 5 TAHUN 2014 TENTANG RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM - Nuratisyah Nuratisyah; Dessy Artina; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research is related to the implementation of controlling of parking service fees on the side of public roads as regulated in Article 28 Paragraph 1 of the Dumai City Regional Regulation Number 5 of 2014 concerning Parking Service Levies on the Side of Public Roads which is carried out regularly. In the field there are still many legal parking attendants who collect fees that do not comply with the provisions that have been set. Therefore it needs to be studied in a stimulant, First, the supervision of the transportation service of parking attendants on the side of public roads based on the Dumai City Regional Regulation Number 5 of 2014 concerning Parking Service Charges on the Side of Public Roads, Second, the obstacles for the transportation service in carrying out controlling of parking attendants in the city of Dumai, Third, Future surveillance efforts carried out by the transportation agency on parking attendants on the side of public roads based on the Dumai City Regional Regulation Number 5 of 2014 concerning Parking Service Retribution on the Side of Public Roads.This research is a sociological legal research, because it is based on field research, namely by collecting data from observations, interviews, and literature reviews that are related to the problems to be studied assisted by primary, secondary and tertiary data. This study uses qualitative data analysis, produces descriptive data, and concludes with a deductive thinking method.From the results of the study, it is concluded that, First, the controlling of the transportation department of parking collectors on the side of public roads based on the Dumai City Regional Regulation Number 5 of 2014 concerning Parking Service Levies on Public Roads has not been optimal. Second, the inhibiting factors for the transportation agency in carrying out supervision of parking collectors in the city of Dumai are the lack of operational personnel, budget, coordination of related parties, and dishonesty of parking collectors. Third, the future controlling efforts carried out by the transportation service on parking collectors on the side of public roads in the city of Dumai are the addition of operational members to supervise parking collectors, reactivate the coordination team for development, regulation and control of parking on the side of public roads.Keywords: Controlling – Parking Officer - Retribution